Dissolution and Reprecipitation of Garnet during Eclogite-facies Metamorphism; Major and Trace Element Transfer during Atoll Garnet Formation. (15th September 2021) - Kulhánek, Jan; Faryad, Shah Wali; Jedlicka, Radim; Svojtka, Martin
Abstract: Garnet commonly accommodates high contents of Mn + Y + heavy rare earth elements (HREE) that follow Rayleigh fractionation during garnet early growth, with the exception of overstepping nucleation (late crystallization owing to reaction overstepping). Because of this, as the garnet porphyroblasts form mostly in equilibrium with the surrounding matrix, the concentration of these elements continuously decreases towards the porphyroblast rims. Yet rapid changes in the reaction progress of a rock during garnet growth, namely the resorption–dissolution of minerals with high concentrations of Y + REE, may create an anomaly or peak in the mantle or rim of garnet grains. In this study we present an example of the resorption of garnet cores and formation of atoll garnet textures in eclogite from the Krušné hory (in the Saxothuringian tectonic zone of the Bohemian Massif). Based on textural relations, we show that the atoll garnet grains in the studied rocks were formed during the prograde stage from blueschist- to eclogite-facies metamorphism. Preliminary observations showed that the full (non-atoll) garnet grains had compositionally different cores (interior, or garnet I) and rims (ring, or garnet II) that were separated by a Y + HREE + medium REE (MREE) concentration peak. The ring garnet II indicated an elevated concentration of Mn in comparison with the marginal parts of the interior garnet I. Therefore, minor elements that were less vulnerable to diffusion than major elements and strongly sensitive to the broad spectrum of geochemical processes, such as Y + REE, were used to track possible mineral reactions during the whole garnet growth path. Thermodynamic modelling indicated the formation of garnet by the breakdown of chlorite and lawsonite/zoisite, and peak-pressure phases were represented by garnet, omphacite, quartz, amphibole, rutile, and talc. To quantify the sources of high Mn concentrations in garnet II and of the Y + HREE + MREE sharp peaks, the sequences of mineral reactions and dissolution of garnet I leading to the formation of the atoll structure were investigated. In addition to thermodynamic modelling and pressure–temperature path constraints, mass-balance calculations of trace elements were also performed. The results combined with the observed compositional and textural relations indicate that the concentrations of Mn + Y + HREE + MREE in garnet II and the concentration peaks at the interface of the two garnet types were controlled by a complex mechanism that included the dissolution of garnet I during the formation of the atoll texture, stepwise growth of garnet during increasing pressure and temperature, and decomposition of phases with high concentrations of trace elements, such as zoisite/epidote or lawsonite.